Rysunki Johanna Christiana Schreibera – toruńskiego artysty amatora z XVIII wieku - Tylicka, Teresa (Sztuka i Kultura, 2016)
The collection of the State Archive in Toruń, consisting of, among others, numerous 18th century topographical documents, includes also a number of drawings originating from the dispersed collection of Johann Jacob Haselau, born in Gdańsk and educated in Leipzig, a humanist and pastor of the Old Town Lutheran Commune in Toruń, where he lived from 1763. He joined the local Protestant intellectual elite displaying vast spiritual, intellectual and artistic interests, which included the clergy, the professors of local Academic Gymnasium and the journalists of Thornische Wöchentliche Nachrichten und Anzeigen weekly. Pastor Haselau – a bibliophile and a collector – assembled an impressive library and a considerable quantity of maps, plans, illustrations and drawings, which in 1774 he had bound into an “artificial atlas”, named: Tabularum topographicarum secundum seriem alphabeticam dispositarum collectio quinque voluminibus comprehensa Thorunii. Four atlas volumes, including views and plans of towns and settlements arranged in alphabetical order from A to Z, have been preserved in the Toruń Archive, while its fifth volume has disappeared and it is not known at present of what illustrations was its contents composed. A part of drawings and prints pertaining to Toruń, inserted originally in volume four was cut out from it in 1914 for “better restoration” and is now kept in various portfolios in the archive. This group contains, among others, six city and interior views made by Johann Christian Schreiber, an amateur draughtsman, and a furrier by profession, baptized in Toruń in 1766, who after apprenticeship in various distant locations returned to his home town. Haselau used to insert handwritten commentaries in various volumes and on particular drawings from his collection, which enable their identification nowadays; this is also the case of drawings made by Schreiber. The earliest of them, depicting the eastern side of Żeglarska street in Toruń, was sketched by the author in 1783, when he was only seventeen years old. Five next images were drawn in 1785, presumably on a special request of the pastor, as they represent interior details of the church of his Lutheran congregation on the Old Market Square (now Roman Catholic church of the Holy Spirit). The drawings depict a general view of the interior, the main altar, the pulpit (twin view), and the baptismal font. Pastor Haselau must have been impressed by the young man’s talent, because he remarked twice in his comments that the illustrations were made by Schreiber without using a ruler, nor compass. Despite the fact that the sketches do not exhibit high artistic level, they may be regarded as a significant source for iconography and history of the town in the 18th century.